HUBUNGAN KETANGGUHAN DENGAN KESEJAHTERAAN PSIKOLOGIS MAHASISWA PEREMPUAN YANG MERANTAU DARI LUAR PROVINSI JAWA TIMUR - Milka Malva Rohi (Perpustakaan Universitas Surabaya, 2018)
Migrating to another province is now usually happened in emerging adulthood female college students. Psychological well-being becomes a matter of concern in the life of female migrants because it deals with the best conditions in the individual arising from positive attitudes to achieve what is expected when dealing with situations in life. Hardiness becomes one of the important capital to achieve psychological well-being because hardiness contains intrinsic aspects of strengths such as; commitment, control, and challenge to be ready for the events that occur and aim for personal growth. This research was using purposive sampling technique with sample of 134 active Ubaya female students from outside East Java province and living in boarding house. Psychological well-being variable was measured by SPWB from Ryff (1989), which was adapted from Abdillah (2016) and the hardiness variable was measured by PVS III-R from Kobasa (2006). Based on the results of the analysis of research data, using non parametric correlation coefficient is ρ = 0,307 with significance level p = 0,000 and effective contribution equal to 12,5%. So it can be concluded that there is a relationship between hardiness with the psychological well-being of female students who migrated from outside East Java Province.